Mengeksplorasi Faktor Penentu Belanja Modal: Studi Kasus Pada Kabupaten/Kota Di Kalimantan Tengah Tahun 2017-2020 - Cristian Zendrato; Puput Iswandyah Raysharie; Alexandra Hukom; Dedi Takari (Manajemen Kreatif Jurnal, 2023)
This study provides an overview of the influence of PAD, DAU, and DAK on Capital Expenditure in districts / cities in Central Kalimantan Province. This research uses the OLS method and in analyzing it uses Multiple Regression Analysis, Eviews 12. The research method used is associative with a quantitative approach. The population in this study were all districts / cities in Central Kalimantan Province. The sample of this study was 56 samples. The data for this study were obtained from the Directorate General of Fiscal Balance (DJPK) APBD realization report 2017-2020. The results of this study are that local revenue has a negative and insignificant effect on capital expenditure and general allocation funds have a positive and significant effect on capital expenditure and special allocation funds have a positive and significant effect on capital expenditure. Meanwhile, simultaneously local revenue, general allocation funds and special allocation funds have a significant effect on capital expenditure. And in this study the more dominant coefficient is the general allocation fund in influencing capital expenditure.